Sistem Pemilihan Kepala Daerah Berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Hasugian, Marudut (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine and examine the meaning contained in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia which states that the Governor, Regent and Mayor respectively as Head of the Provincial, Regency and City Regional Government are elected democratically. The approach method used in this study is normative juridical which is used to discuss this main problem, namely the legislative approach and the conceptual approach. The results of this study prove the birth of the word democratic in Article 18 paragraph (4) of the Constitution when the 1945 Constitution was amended in the MPR General Session in 2000, where there were 2 (two) different opinions regarding the method of electing regional heads, one requiring direct elections by the people or the other being elected by the DPRD. The agreement on the democratic formulation for regional elections was achieved with the intention of being flexible. So that the Lawmakers can formulate the election system desired by the community in the election of regional heads so that the community has a choice by the DPRD or direct election by the people. This is also intended as a form of constitutional respect for the diversity of customs and cultures of communities between different regions. As regulated in Article 18B of the 1945 Constitution of the Republic of Indonesia which recognizes regional government units that are special and special and recognition of the unity of customary law communities. This is supported by the Constitutional Court Decision Number 072-073/PUUII/2004 and the Constitutional Court Decision Number 97/PUU-XI/2013, which explains the background of the thinking behind the formulation of Article 18 paragraph (4) of the 1945 Constitution at that time, the regional head election system that will be implemented is adjusted to the development of society and conditions in each region concerned. The goal is to adjust to the dynamics of national development to determine the democratic system desired by the people.